The Effectiveness of Covid-19 Vaccine Education on The Knowledge and Attitudes of PKK Cadres in Wanajaya Village, Wanaraja District – Garut - Genialita Fahdilla; Risa Susanti; Siti Fatimah; Tami Novia Utami (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstract The Coronavirus Disease (COVID-19) pandemic in Indonesia has been lasting for almost 2 years. The increasing number of Covid-19 cases in Indonesia has made the government in several regions continue to take steps to contain the spread of Covid-19, one of which is by carrying out Covid-19 vaccinations. People's views and knowledge about the Covid-19 vaccine are diverse, including in terms of safety guarantees, requirements for receiving vaccines, doubts about the effectiveness and efficacy of the vaccine itself. Some of which even refuse to be vaccinated and it is common for people to show distrust towards vaccines, due to lack of information. Therefore, this dedication was conducted to assess the effect of Covid-19 vaccine education on the knowledge and attitudes of PKK cadres in Wanajaya Village, Wanaraja Regency. The research method used was the pre-experimental study design with the One Group Pretest-Posttest design with the sampling technique used was purposive sampling. The dedication was conducted using an instrument in the form of a questionnaire given before and after educational. The results of the Wilcoxon and Paired Sample T-Test analysis showed that the education given to the respondents had an effect on the knowledge and attitudes of respondents with a value of p = 0.000 (p <0.05). From this dedication, it could be concluded that there were significant differences in respondents knowledge and attitudes before and after being given education, meaning that the education given to respondents is effective or influence on the knowledge and attitudes of respondents. Abstrak Pandemi Coronavirus Disease (COVID-19) di Indonesia telah berlangsung hampir 2 tahun. Peningkatan kasus Covid-19 di Indonesia yang terus bertambah membuat pemerintah di beberapa daerah terus berupaya melakukan langkah untuk menahan laju penyebaran Covid-19 salah satunya dengan melaksanakan vaksinasi Covid-19. Saat ini pandangan dan pengetahuan masyarakat tentang Vaksin Covid-19 beragam termasuk dalam hal jaminan keamanan, persyaratan penerimaan vaksin, keraguan keefektifan serta keampuhan vaksin sendiri. Beberapa diantaranya menolak untuk divaksin, bahkan tidak jarang masyarakat menunjukan sikap tidak percaya terhadap vaksin, karena kurangnya informasi. Oleh karena itu, pengabdian ini dilakukan untuk menilai efektivitas edukasi vaksin covid-19 terhadap pengetahuan dan sikap ibu-ibu PKK Desa Wanajaya Kecamatan Wanaraja. Metode pengabdian yang digunakan yaitu desain studi Pra-Eksperimen dengan rancangan One Group Pretest-Posttest dengan teknik pengambilan sampel yaitu Purposive Sampling. Pengabdian dilakukan menggunakan instrumen berupa kuesioner yang diberikan sebelum dan sesudah edukasi. Hasil analisis Wilcoxon dan Paired Sample T-Test menunjukan bahwa edukasi yang diberikan kepada responden berpengaruh terhadap pengetahuan dan sikap responden dengan nilai p = 0,000 (p < 0,05). Dari pengabdian ini dapat disimpulkan bahwa terdapat perbedaan yang signifikan pada responden sebelum dan sesudah diberikan edukasi, artinya edukasi yang diberikan kepada responden efektif atau berpengaruh terhadap pengetahuan dan sikap responden